2017
DOI: 10.1080/10253890.2017.1328494
|View full text |Cite
|
Sign up to set email alerts
|

Buccal telomere length and its associations with cortisol, heart rate variability, heart rate, and blood pressure responses to an acute social evaluative stressor in college students

Abstract: Consistent with predictions, greater reductions in HR variability (HRV) in response to a stressor and greater cortisol output during the study session were associated with shorter relative buccal telomere length (i.e. greater cellular aging). However, the relationship between cortisol output and buccal telomere length became non-significant when adjusting for medication use. Contrary to past findings and study hypotheses, associations between cortisol, blood pressure, and HR reactivity and relative buccal telo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 41 publications
5
24
0
Order By: Relevance
“…The present finding that HF‐HRV decreased during the math stressor is consistent with many previous investigations employing math tasks as stressors (Petrowski et al, ; Wagner et al, ; Whited et al, ; Winzeler et al, ; Woody et al, ). Given that present findings also indicate an increase in HR during the math stressor, present findings further suggest that parasympathetic withdrawal contributes to HR acceleration commonly found during these types of stressors (Bandler et al, ; Kelsey, ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present finding that HF‐HRV decreased during the math stressor is consistent with many previous investigations employing math tasks as stressors (Petrowski et al, ; Wagner et al, ; Whited et al, ; Winzeler et al, ; Woody et al, ). Given that present findings also indicate an increase in HR during the math stressor, present findings further suggest that parasympathetic withdrawal contributes to HR acceleration commonly found during these types of stressors (Bandler et al, ; Kelsey, ).…”
Section: Discussionsupporting
confidence: 92%
“…The math portion of the TSST was used to as the sensory rejection stressor. Research has shown that the TSST reliably induces an increase in HR and a decrease in HF‐HRV (Petrowski et al, ; Woody et al, ) and instigates a significant stress response (Het, Rohleder, Schoofs, Kirschbaum, & Wolf, ). Participants were observed via camera with the researchers in a separate room.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This also helps to understand why TL and HRV may be directly related to each other and inversely related to organ failure (i.e., nocturnal polyuria) and why these variables might be related for this current patient. Woody, et al reported "greater reductions in HRV in response to a stressor are associated with shorter relative TL (i.e., greater cellular aging)" [45]. Additionally, improvements in objective health measures (spinal alignment and posture, HRV, nocturnal polyuria, and TL) are directly related to the subjective improvements in the patient's health (pain NRS and QoL).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this study included only perfectionist participants and incorporated three control conditions (general mindfulness, progressive muscle relaxation [PMR], and no instruction). When presented with an evaluative stressor (e.g., mental arithmetic under evaluation), HF‐HRV will typically decrease relative to baseline and recover to baseline levels after the task is completed (e.g., Kelsey, ; Petrowski et al, ; Pulopulos, Vanderhasselt, & De Raedt, ; Woody, Hamilton, Livitz, Figueroa, & Zoccola, ). However, Azam and colleagues () found that for nonperfectionistic participants, HF‐HRV increased beyond baseline levels, suggesting that mindfulness meditation may promote more relaxation than observed at baseline.…”
Section: Introductionmentioning
confidence: 99%